Smart Surveillance System for Automatic Detection of License Plate Number of Motorcyclists without Helmet - Ghonge, Sneha A; Sanghavi, Jignyasa B (International Journal of Computer Sciences and Engineering, 2025)
Since, motorcycles are affordable and a daily mode of transport there has been a rapid increase in motorcycle accidents, due to the fact that most of the motorcyclists do not wear a helmet which has made it an ever-present danger every day to travel by motorcycle. In last couple of years Government has made it a punishable offense to ride a motorcycle without helmet. The existing video surveillance based system is effective but it requires significant human assistance whose efficiency decreases with time and human biasing also comes into picture. So, automation of this process is highly desirable. In this paper, we propose an approach for automatic detection of motorcyclists without helmet using surveillance videos in real-time .The proposed approach first detects the motorcycle from the surveillance videos using background subtraction. Then it classifies between helmet and non-helmet using 1st order and 2nd order derivative edge detection algorithm and neural network. After detection if the motorcyclists are found without helmet then it will trace the vehicle number plate of the motorcyclists using (OCR) Optical Character Recognition and Neural Network and a copy of challan will be generated and will be send via SMS to the respective traffic rule violator.